2018
DOI: 10.17219/acem/66385
|View full text |Cite
|
Sign up to set email alerts
|

Methodological exploration of bone marrow stem cell therapy in acute myocardial infarction – how to achieve greater benefit on cardiac outcomes: A systematic review and meta-analysis

et al.

Abstract: Methodological differences in BMCs preparation as well as the use of heparin and serum/ plasma impact on the prognosis of AMI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…In addition to the dose controversy, methodologies for cell preparation also have impacts on the prognosis of AMI patients. A systematic review on methodology showed that nonuse of serum or plasma in the cell suspension is associated with a greater reduction in infarct size and a lower risk of all-cause mortality, and heparin usage could diminish the benefit in reducing IS ( Yang et al, 2018 ). Therefore, a well-designed randomized control trial with unified cell preparation and administration doses, as well as rigorous evaluations of cardiac function and long-term clinical outcome follow-up, are required to further establish a clear risk-benefit profile of MSCs.…”
Section: Clinical Trials Using Bmmscs For Ischemic Heart Diseasementioning
confidence: 99%
“…In addition to the dose controversy, methodologies for cell preparation also have impacts on the prognosis of AMI patients. A systematic review on methodology showed that nonuse of serum or plasma in the cell suspension is associated with a greater reduction in infarct size and a lower risk of all-cause mortality, and heparin usage could diminish the benefit in reducing IS ( Yang et al, 2018 ). Therefore, a well-designed randomized control trial with unified cell preparation and administration doses, as well as rigorous evaluations of cardiac function and long-term clinical outcome follow-up, are required to further establish a clear risk-benefit profile of MSCs.…”
Section: Clinical Trials Using Bmmscs For Ischemic Heart Diseasementioning
confidence: 99%
“…Stem cell therapy is a novel treatment paradigm that has been pursued more in the past few years in both basic science and in the clinic. This treatment is being used to regenerate tissues after disease in neurological and cardiac diseases as well as osteoarthritis . We have previously shown that small cholangiocytes, which may contain a subpopulation of biliary progenitor cells, reduced fibrotic scarring in bile duct ligation (BDL) mice through activation of forkhead box A2 (FoxA2) …”
mentioning
confidence: 99%
“…This treatment is being used to regenerate tissues after disease in neurological and cardiac diseases as well as osteoarthritis. (6)(7)(8) We have previously shown that small cholangiocytes, which may contain a subpopulation of biliary progenitor cells, reduced fibrotic scarring in bile duct ligation (BDL) mice through activation of forkhead box A2 (FoxA2). (9) MicroRNAs (miRNAs) are small noncoding RNAs that can regulate gene expression through direct binding to mRNA or DNA.…”
mentioning
confidence: 99%